Video Steganography Encryption on Cloud Storage for Securing Digital Image - Prasetyo, Chrisna Joshua Sergio; Suputra, I Putu Gede Hendra; Putri, Luh Arida Ayu Rahning; Widiartha, I Made; Suhartana, I Ketut Gede; Karyawati, Anak Agung Istri Ngurah Eka (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2022)
Cloud storage is a data storage service in cloud computing that allows stored data to be shared and accessed via the internet. Cloud storage is usually used to store personal data such as files, photos, or videos with so that these data can be accessed anywhere via the internet without the need to use physical storage media. However, cases of data leaks in cloud storage still occur which causes personal data stored in cloud storage to be accessed by other people who do not have access. The Client-Side Steganography Encryption on Cloud Storage Application was developed using the Modified Least Significant Bit (LSB) method and the Standard Advanced Encryption (AES) algorithm. This desktop-based application was developed to protect personal data of digital images embedded in a video so that unauthorized parties cannot view the data. This application is expected to be a data security solution on cloud storage to prevent theft of personal data by non-existent parties. From the test results, the developed application can receive input, process input, and produce the desired output. The image from the extraction process from video also does not change at all in terms of visual or visible. The results obtained from this test is the PSNR value with an average of 36,395 dB. A good PSNR value is above 30 dB and indicates that the quality of the extracted image is good and also indicates that the developed application can protect data of digital images into video.